Population Control in Nigeria: The Role of Information Disseminator - Akanwa, Pearl; Anyanwu, Emmanuel Uwazie; Ossai-Onah, Oyemike Victor (MiddleBelt Journal of Library and Information Science, 2013)
The paper X-rays the role of the information disseminator in population control and the implication the paper identifies and discussed some major issues on the concept of over-population, causes of over-population such as cultural beliefs, early marriage, low level of literacy/ poor orientation and effects of overpopulation such as high rate of unemployment, high level of poverty, high demand of health facilities were explored. The strategies the information disseminator applied in ensuring the people are better informed about population control were also discussed. Recommendations were put forward.